Effectiveness of housing design features in malaria prevention: architects’ perspective - Chisumbe, Sampa; Aigbavboa, Clinton; Akinradewo, Opeoluwa; Mukeya, Gideon (Frontiers in Built Environment, 2024)
The purpose of this research was to assess housing design consideration features, and Architects' perception, on their effectiveness in malaria prevention. The methodological approach adopted was quantitative in nature, with data collected using a structured questionnaire containing closed ended questions as well as a checklist. The observation checklist was used in ascertaining mosquito entry reduction features incorporated in 208 systematically selected houses of Garneton East, Kitwe, Zambia. Whereas a structured questionnaire containing fourteen key design features identified from literature was administered to 76 Architects purposively sampled in establishing Architects perception on the effectiveness of design factors in malaria prevention. Data collected was analysed using descriptive statistics as well as exploratory factor analysis. The findings revealed that most houses had not incorporated necessary design features aimed at reducing mosquito entry. The common features incorporated were ceilings (86.80%), screened air ventilations (59.80%) and window screens (54.40%). The use of window and door screens, as well as mosquito repellent paint were perceived most effective. The results suggest keen awareness by Architects on the efficacy of design features, further, the use of housing to reduce malaria morbidity and mortality requires greater effort. The study therefore recommends that building regulations be adaptive by providing for and promoting the use of mosquito entry reduction features in housing designs.